Traditional Chinese Medicine, Qingfei Paidu Decoction and Xuanfei Baidu Decoction, Inhibited Cytokine Production via NF-κB Signaling Pathway in Macrophages: Implications for Coronavirus Disease 2019 (COVID-19) Therapy - Li, Yujia; Li, Bin; Wang, Pan; Wang, Qinghua (Frontiers in Pharmacology, 2021)
Background & Aims: Qingfei Paidu decoction(QPD) and Xuanfei Baidu decoction(XBD) are two typically traditional Chinese medicines with proven efficacy for the treatment of coronavirus disease 2019, although the underlying mechanism is not well defined. Blunted immune response and enhanced production of pro-inflammatory cytokines (cytokine storm) are two main features observed in patients infected with SARS-CoV-2. Network pharmacology-based analysis revealed that both QPD and XBD played an important role in the regulation of host immunity. We therefore investigated the role of QPD and XBD in the modulation of innate immunity in vitro, focusing on type I interferon(IFN) signaling pathway in A549 cells and pro-inflammatory cytokine production in macrophages. Methods: A549 cells were treated with QPD or XBD and the production of endogenous IFNα and IFNβ as well as the expression levels of some interferon-stimulated genes (ISGs) were detected by reverse transcriptase-quantitative PCR (RT-qPCR). THP-1-derived macrophages were treated with QPD or XBD and the pro-inflammatory cytokine expression levels were measured by RT-qPCR 6 hours post LPS stimulation. In addition, some of the differentially expressed genes were further confirmed by western blot or ELISA. The effect of QPD and XBD on NF-κB signaling pathway and pinocytosis activity of THP-1-derived macrophages were evaluated by western blot and netrual red uptake experiment, respectively. Results: Although QPD and XBD showed very little effect on type I IFN signaling pathway, either QPD or XBD markedly inhibited the production of pro-inflammatory cytokines including Interleukin-6, tumor necrosis factor-α, monocyte chemotactic protein-1 and chemokine ligand 10 in M1 THP-1-derived macrophages. In addition, The phosphorylation of IκBα and NF-κBp65 during polarization was significantly suppressed following QPD or XBD treatment in macrophages. QPD and XBD also suppressed the pinocytosis activity of macrophages. Conclusion: QPD and XBD have been shown to have robust anti-inflammatory activities in vitro. Our study demonstrated that both QPD and XBD decreased pro-inflammatory cytokines expression, inhibited the activation of NF-κB signaling pathway and blunted pinocytosis activity in M1 THP-1-derived macrophages